NCAA strength and conditioning coach demographics, current practice trends and common injuries of athletes during strength and conditioning sessions - Waryasz, G. R.; Daniels, A. H.; Gil, J. A.; Suric, V.; Eberson, C. P. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: NCAA strength and conditioning coaches are responsible for the day-to-day conditioning and strength training of collegiate athletes. NCAA regulations will likely require all strength and conditioning coaches to have a strength and conditioning certification. NCAA strength and conditioning coaches have varied philosophies on exercise programming based on educational background. The study aims to further evaluate the backgrounds and exercise philosophies of NCAA strength and conditioning coaches.